Epidemiology of human immunodeficiency virus-visceral leishmaniasis-co-infection - Naufal Spir, Patrícia Rodrigues; Zampieri D'Andrea, Lourdes Aparecida; Fonseca, Elivelton Silva; Prestes-Carneiro, Luiz Euribel (Elsevier, 2013)
In Brazil, the rates of mother-to-child-transmission (MTCT) of human immunodeficiency virus (HIV) decreased from 20% to 1-2% in some regions. However, the country contains 90% of individuals infected with visceral leishmaniasis (VL) in Latin America, and the west region of São Paulo state faces an alarming expansion of the disease. We describe the epidemiological aspects of the expanding infection of VL and a case report of an HIV-VL-co-infected child from the west region of São Paulo state. The patient was an AIDS-C3 with low levels of CD4, high viral load, severe diarrhea, oral and perineal candidiasis, severe thrombocytopenia, and protein-caloric malnourishment. She evolved with sepsis, renal and cardiac failure. An rK rapid diagnosis test, indirect fluorescent antibody test (IFAT), and bone marrow aspirate were performed for VL. Her symptoms improved significantly after liposomal amphotericin B administration. From the 45 municipalities that compose the Regional Health Department of Presidente Prudente, Lutzomyia longipalpis vectors were found in 58% of them. VL infected dogs were found in 33% of those municipalities, infected dogs and humans were found in 29%, 20% are starting and 33% of the municipalities are preparing VL investigation. It is likely, in this patient, that VL advanced the clinical progression of the HIV disease and the development of AIDS severity. Supported by favorable conditions, the region becomes a new frontier of VL in Brazil. © 2013.
Keywords: AIDS; HIV; HIV-VL-co-infection; Visceral leishmaniasis